2003
DOI: 10.1002/elps.200305606
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic dynamics of large DNA stars in polymer solutions and gels

Abstract: We have developed a procedure for synthesizing large stable branched DNA structures that enables visualization via fluorescence microscopy. Using this procedure we have synthesized large DNA stars and observed their electrophoretic behavior in polymer solutions and gels. In dilute polyacrylamide solutions, the DNA stars move as random coils and appear to experience only brief collisions with the polymer chains in solution. The effect of polymer solution concentration on the electrophoretic mobility of stars in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…On this basis they suggested that the transition from U-to I-shaped motion could be induced by the degree of entanglement among polymer chains. In our previous study [17] we found that starbranched DNA also undergoes a series of conformational changes which were somewhat similar to the U-to I-shape transition observed for linear DNA in semidilute polymer solution. Whereas in fixed networks, star-branched DNA is observed to become trapped near the well, a consequence of the branch point [17].…”
Section: Videomicroscopymentioning
confidence: 66%
See 3 more Smart Citations
“…On this basis they suggested that the transition from U-to I-shaped motion could be induced by the degree of entanglement among polymer chains. In our previous study [17] we found that starbranched DNA also undergoes a series of conformational changes which were somewhat similar to the U-to I-shape transition observed for linear DNA in semidilute polymer solution. Whereas in fixed networks, star-branched DNA is observed to become trapped near the well, a consequence of the branch point [17].…”
Section: Videomicroscopymentioning
confidence: 66%
“…Electrophoretic mobility of large linear and star DNA was measured using a custom-made visualization cell [17]. Measurements of the steady-state center-of-mass velocity v of fluorescently labeled DNA in semidilute LPA solutions were obtained using an intensified CCD camera (Video Scope Maxicam 3000) and image processing software (Image Pro).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent staining using an intercalating cyanine dye, YoYo-1 (Molecular Probes), permits direct visualization of the branched DNA molecules. 24,25 In the approach used by Heuer et al, 25 DNA branched structures are synthesized using immobile nucleic acid junctions. These junctions are DNA structures where three or more double-helical strands branch out from a central point.…”
Section: Visualizing Relaxation Dynamics Of Molecules Near Surfacesmentioning
confidence: 99%